Coreceptor blockade targeting CD4 and CD8 allows acceptance of allogeneic human pluripotent stem cell grafts in humanized mice. (July 2020) - Li, Jiatao; Li, Xisheng; Liang, Cai; Ling, Lijun; Chen, Zhiwei; Wong, Chun Kwok; Waldmann, Herman; Lui, Kathy O.
Abstract: We have previously demonstrated that short-term coreceptor blockade with non-lytic monoclonal antibodies enables the long-term survival of fully allogeneic embryonic stem cell (ESC) transplants in mice. Here, we describe the use of Hu-PBL humanized mice to determine whether short-term coreceptor blockade with humanized anti-human CD4 and CD8 antibodies can achieve the same outcome towards human ESC derivatives. While control Hu-PBL mice rejected allogeneic hESC-derived transplants within weeks, mice treated with coreceptor blocking antibodies held their grafts for 7 weeks, the duration of the study. Rejection in the control mice was associated with demonstrable infiltrates of human CD45 white blood cells, predominantly of CD8 T-cells, whereas anti-CD4, but not anti-CD8 antibody treated mice showed remarkably reduced lymphocyte infiltration and prolonged allograft survival, indicating that the CD4 + T-cells were crucial to the rejection process. Our results give support to the principle that short-term blockade of T-cell co-receptors can achieve long-term acceptance of regenerative cell transplants in humans.